Water enables mild oxidation of methane to methanol on gold single-atom catalysts - Luo, Laihao; Luo, Jie; Li, Hongliang; Ren, Fangning; Zhang, Yifei; Liu, Andong; Li, Wei-Xue; Zeng, Jie (Nature communications, 2021)
As a 100% atom-economy process, direct oxidation of methane into methanol remains as a grand challenge due to the dilemma between activation of methane and over-oxidation of methanol. Here, we report that water enabled mild oxidation of methane into methanol with >99% selectivity over Au single atoms on black phosphorus (Au 1 /BP) nanosheets under light irradiation. The mass activity of Au 1 /BP nanosheets reached 113.5 μmol g catal −1 in water pressured with 33 bar of mixed gas (CH 4 :O 2 = 10:1) at 90 °C under light irradiation (1.2 W), while the activation energy was 43.4 kJ mol −1 . Mechanistic studies revealed that water assisted the activation of O 2 to generate reactive hydroxyl groups and •OH radicals under light irradiation. Hydroxyl groups reacted with methane at Au single atoms to form water and CH 3 * species, followed by oxidation of CH 3 * via •OH radicals into methanol. Considering the recycling of water during the whole process, we can also regard water as a catalyst. It is important but challenging to oxidize methane by O 2 into methanol under ambient conditions. Here, the authors achieved mild oxidation of methane into methanol over Au single atoms on black phosphorus nanosheets with the help of water under light irradiation.